To Punish or Reintegrate? Balancing Legal Protection and the Future of the Child Terrorist - Khalid, Ihab Natiq; Hassan, Muhamad Sayuti; Md Said, Muhammad Helmi (Faculty of Law, Universitas Brawijaya, 2024)
In West Asia regions such as Iraq and Syria, children are vulnerable to terrorists, especially the Islamic State of Iraq and Syria (ISIS). Iraq has suffered years of massacre by ISIS using children recruited and transformed into “lions”. This resulted in the enactment of the Iraqi Anti-Terrorism Law in 2005 to address the menace. However, this law did not distinguish between adult offenders and child offenders; rather, it issued general punishment for the crime of terrorism. The study aims to determine the justification for punishment for child terrorists in light of the surrounding circumstances of indoctrination and transformation into dehumanized humans. Studies on child recruitment by ISIS, child soldiers, and ISIS and children were collected and analyzed using doctrinal legal analysis. The findings were thematically analyzed and discussed accordingly. It was discovered that justification for the punishment of children recruited by ISIS would be more effective when certain factors like the method of child recruitment are examined, the experiences of the children, and the impact the recruitment has had on the recruited children to avoid recidivism. That has turned them into terrorists and lacking human sympathy. This study suggests the need to punish these children under the provision of Juvenile Welfare Care with the purpose of de-radicalizing, rehabilitating, and reintegrating them into society while considering the safety of the community. Relevant strategies are essential for safeguarding the future of children and protecting their human rights.